(untitled) (GUB Journal of Science and Engineering, 2022)
Bangladesh’s clothing industry is the backbone of the country’s economy. One of the most crucial first phases in the apparel industry is to create and develop garment patterns based on the anticipated apparel’s specifications, and then to plan the marker and cut the fabric according to the pattern pieces. These can be done manually or with the use of Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM) software (CAM). The garment business has been transformed by computer-aided design (CAD) and computer-aided manufacturing (CAM). Because fabric costs account for a large portion of the cost of garment manufacture, it is critical to properly utilize the fabric and reduce the percentage of fabric waste (percent). Additionally, minimizing production time will reduce lead time even more. Although CAD/CAM is expensive, it has a number of economic and technological advantages over other methods. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 8, Dec 2021 P 36-40